Czy nadszedł czas wielkich pytań? - Zanussi, Krzysztof (Annales. Etyka w Życiu Gospodarczym, 2009)
One thing we cannot do is failing to address the issue of ‘what next’? Where are we heading? What are our objectives on the horizon of dreams and not short-term solutions? Where is mankind heading as a whole? It is you economists and managers I am aiming my questions at. I am incapable of finding a clear answer but I sincerely hope to discover it in your dissertations (going beyond your master, doctorate and habilitation theses).Thanks to the brilliant paradigm, our civilisation has made achievements which it tends to forget. Mankind today is living more comfortably than ever before. I want to raise a question if we are conscious of the fact that our privileges should be shared by all inhabitants of our planet.I wish to reflect on the good of a man – what does a human need to be fulfilled in all dimensions, not in the mere material one. How do we conceive of the future organization and identity of mankind? I asked school principals: Is it good to allow the sexes to become alike, to see women become masculine and men effeminate? Is the contrast of the sexes vital to the preservation of the human race? Does the tension resulting from the diversification matter? I do not intend to present my own intuitions; my wish would be finding some answers in humanities. Sadly, doctorate and habilitation theses tend to focus on marginal issues.Why does contemporary theology differ so considerably from what the contemporary world, contemporary physics or mathematics deal with on a regular basis?